2006
DOI: 10.1126/science.1115035
|View full text |Cite
|
Sign up to set email alerts
|

Caspases 3 and 7: Key Mediators of Mitochondrial Events of Apoptosis

Abstract: The current model of apoptosis holds that upstream signals lead to activation of downstream effector caspases. We generated mice deficient in the two effectors, caspase 3 and caspase 7, which died immediately after birth with defects in cardiac development. Fibroblasts lacking both enzymes were highly resistant to both mitochondrial and death receptor-mediated apoptosis, displayed preservation of mitochondrial membrane potential, and had defective nuclear translocation of apoptosis-inducing factor (AIF). Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
789
5
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,042 publications
(862 citation statements)
references
References 22 publications
54
789
5
3
Order By: Relevance
“…Despite there are limited information about caspase-6 and -7 rather than caspase-3, it is known that while caspase-3 suppression results in the inhibition of apoptosis, suppression of caspase-6 and -7 do not significantly affect the apoptotic process [48]. Furthermore, caspase-3 was reported to be crucial for PARP cleavage and DNA fragmentation which are hallmarks of apoptosis [49]. However, some studies showed that under the conditions that both caspase-3 and caspase-7 were knocked out, the cells could undergo cell death in an alternative manner via necrosis.…”
Section: Caspase Family Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite there are limited information about caspase-6 and -7 rather than caspase-3, it is known that while caspase-3 suppression results in the inhibition of apoptosis, suppression of caspase-6 and -7 do not significantly affect the apoptotic process [48]. Furthermore, caspase-3 was reported to be crucial for PARP cleavage and DNA fragmentation which are hallmarks of apoptosis [49]. However, some studies showed that under the conditions that both caspase-3 and caspase-7 were knocked out, the cells could undergo cell death in an alternative manner via necrosis.…”
Section: Caspase Family Membersmentioning
confidence: 99%
“…However, some studies showed that under the conditions that both caspase-3 and caspase-7 were knocked out, the cells could undergo cell death in an alternative manner via necrosis. Studies with caspase-3/caspase-7 double-knockout thymocytes and mouse embryonic fibroblasts showed that thymocytes remain sensitive to Fas-mediated apoptosis, whereas fibroblasts become resistant [49,50].…”
Section: Caspase Family Membersmentioning
confidence: 99%
“…However, executioner caspases were found to be required for full-blown Bax activation and mitochondrial permeabilisation in response to diverse stimuli. 19 In addition, when caspase activity is blocked, subsets of mitochondria remain refractory to permeabilisation and allow cells to survive to death stimuli. 20,21 Thus, caspase activity might also amplify the apoptotic process upstream of mitochondria, and fuel signals initiated by inhibition of some Bcl-2 homologs by ill-characterized mechanisms.…”
mentioning
confidence: 99%
“…Recently, it has been reported that MEFs derived from mice either deficient for caspase-9 or doubly deficient for caspase-3 and caspase-7 show a delay in cytochrome c release following UV irradiation, implicating a role for caspase feedback at the mitochondria in regulating cytochrome c release. 30 In contrast, in sympathetic neurons, which are dependent solely on caspase-3 for effector caspase activity, deletion of caspase-3 did not alter the kinetics of cytochrome c release following NGF deprivation (Supplementary Figure 2). These results suggest that the role for caspase-mediated feedback on mitochondrial release of cytochrome c may be cell type or stimulus specific.…”
Section: Discussionmentioning
confidence: 91%